Insights into refractory chronic inflammatory demyelinating polyneuropathy: a comprehensive real-world study - Zheng, Yongsheng; Hu, Jianian; Sun, Chong; Qiao, Kai; Zhao, Yanyin; Liu, Bingyou; Sun, Jian; Xi, Jianying; Luo, Sushan; Lu, Jiahong; Zhao, Chongbo; Lin, Jie (Frontiers in Neurology, 2024)
Background: Refractory chronic inflammatory demyelinating polyneuropathy (CIDP) is a challenging subset of CIDP. It does not respond well to immune therapy and causes substantial disability. A comprehensive understanding of its clinical profile, electrophysiological characteristics and potential risk factors associated with refractoriness remains to be further elucidated.Methods: Data in this cross-sectional study was collected and reviewed from the Huashan Peripheral Neuropathy Database (HSPN). Included patients were categorized into refractory CIDP and nonrefractory CIDP groups based on treatment response. The clinical and electrophysiological characteristics were compared between refractory and non-refractory CIDP groups. Potential risk factors associated with refractory CIDP were explored with a multivariate logistic regression model.Fifty-eight patients with CIDP were included. Four disease course patterns of refractory CIDP are described: a relapsing-remitting form, a stable form, a secondary progressive form and a primary progressive form. Compared to non-refractory CIDP patients, refractory CIDP exhibited a